New tool for the simultaneous detection of 10 different genotypes of Acanthamoeba available from the American Type Culture Collection. Issue 8 (28th April 2009) - Goldschmidt, P; Degorge, S; Benallaoua, D; Saint-Jean, C; Batellier, L; Alouch, C; Laroche, L; Chaumeil, C
Abstract : Background: Acanthamoeba keratitis (AK) is a sight-threatening infection, and none of the current diagnosis tests are able to detect in one reaction low levels of the vast majority of strains associated with pathology. The goal of this work was to validate a new tool for the detection of the American Type Cell Collection (ATCC) referenced Acanthamoeba monitoring simultaneously DNA extraction yields and PCR inhibitors. Performances were assessed on corneal scrapings. Methods: Primers were selected in a region bracketing a 41 591 bp of the A castellanii mitochondrion gene. DNA extraction and PCR inhibitors were monitored by adding an internal control (virus). Acanthamoeba were detected and quantified by the real-time fast-duplex TaqMan PCR (f-d-real-t PCR) and negativity confirmed by SYBR Green real-time PCR. Results: The f-d-real-t PCR detects 0.1 cyst/μl or less of the 10 referenced strains (sensitivity slightly lower for A astronyxis ). Bacteria, fungi and herpesviruses do not cross-react. The specificity and sensitivity of the f-d-real-t PCR were higher than culture and other real-time PCR on 20 keratitis samples. Conclusion: The f-d-real t PCR detects in less than 2 h the Acanthamoeba strains available from the ATCC with a higher sensitivity and specificity than techniques previously reported. Larger trials are necessary to validate its usefulness for disease management and environmental studies.